OBSERVATIONS ON THE BIOLOGY OF LABEO GONIUS (HAMILTON) - Parameswaran, S; Selvaraj, C; Radhakrishnan, S (Indian Journal of Fisheries, 2011)
Observations on the biology of Labeo gonius (Hamilton) in confined waters have been made and the data on the different aspects have been analyzed and discussed. The length - weight relationship of the species can be expressed by the equation US’=0.000007153 L 3.0865. The monthly fluctuation in the condition factor of the adult fish was found to be related to the maturity cycle. L. gonius matures within a year. The ratio between males and females was found to be 1:1.052. Macroscopic and microscopic examination of the gonads, ova diameter measurements and gonadosomatic index indicated that mature fish become available from March to August, thÂ© peak being in May. The size frequency of ova in ovaries in different stages of maturity suggested that the species breeds only ones in a year. The statistical relationships between fecundity in relation to total length, total weight and ovary weight and ovary weight in relation to total length have been established. From an exclusively plankton-feeding habit in the post-larval stage, the species changes over to a column and bottom-feeding habit in the juvenile stage, subsisting on vegetable matter, phyto and zooplankton organisms, mud and sand. The adult fish is predominantly a bottom feeder, the diet consisting of fresh and decaying plant matter, mud and sand, phytoplankton and filamentous algae. Preliminary experiments indicated that the growth rate of L. gonius is poor in comparison to major carps.